Critique of: “Basic Concepts for a Theory of Organization” - Stinchcombe, Arthur L. (Management Science, 1967)
A critique of Stogdill, R. M. 1967. Basic concepts for a theory of organization. Management Sci. 13 (10, June) B-666–B-676.